2010
DOI: 10.2355/isijinternational.50.1950
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Alignment of Bi–Sn Alloy by Simultaneous Imposition of a Static Magnetic Field and an Alternating Current during Solidification

Abstract: Crystal alignment of a Bi-10mass%Sn alloy solidified under different electromagnetic field imposing condition has been experimentally investigated in this study. Simultaneous imposition of a static magnetic field and an alternating current excited an electromagnetic vibration and it promoted nucleation, and resulted in decrease of undercooling, though imposition of the static magnetic field alone did not affect the undercooling. Furthermore, grain size of the solidified structure under the simultaneous imposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…When no external magnetic field was applied during the ESR process, the Lorentz force generated by the induced magnetic field and the remelting current was very small, and it could be ignored in our experiments due to the small remelting current. While a large external TSMF was superimposed with the AC current, a forceful electromagnetic vibration (EMV) [26][27][28][29] would be generated. The EMV is the Lorentz force (F = J × B, where J is the current density and B is the magnetic field intensity), whose amplitude and orientation is periodic changed corresponding with the time behavior of the AC current.…”
Section: Droplet Evolution Under Differentmentioning
confidence: 99%
“…When no external magnetic field was applied during the ESR process, the Lorentz force generated by the induced magnetic field and the remelting current was very small, and it could be ignored in our experiments due to the small remelting current. While a large external TSMF was superimposed with the AC current, a forceful electromagnetic vibration (EMV) [26][27][28][29] would be generated. The EMV is the Lorentz force (F = J × B, where J is the current density and B is the magnetic field intensity), whose amplitude and orientation is periodic changed corresponding with the time behavior of the AC current.…”
Section: Droplet Evolution Under Differentmentioning
confidence: 99%
“…6) On the other hand, solidification under a magnetic field has also been reported to directly yield crystal aligned structures in various alloys. [20][21][22][23][24][25][26][27][28][29][30][31][32] Iwai and Usui 20) showed that the c-axis of the Bi-rich primary phase in Bi-10 mass % Sn alloys can be aligned by simply applying a 8 T magnetic field during solidification. Legrand et al 21) succeeded in forming highly c-axis aligned Sm-Co alloys by applying a 2.5 T magnetic field during rapid solidification.…”
Section: Introductionmentioning
confidence: 99%